Biometric analysis of facial features and arch dimensions of Malaysian malay / Heba Abdul Karim Mohammad - Abdul Karim Mohammad, Heba (2011)
Many researchers tried to define and prove certain correlation between the different components of biometric, anatomical landmarks and facial features of different ethnics Groups. However, these studies may be specific for an ethnic group and cannot always be applied for others. The aim of this study is to evaluate the biometric and radiographic analysis of the craniofacial skeleton in both genders of Malaysian Malay. The method involved clinical examination, collection and analysis of dental casts and lateral cephalometric radiograph of Mala ysian Malay subjects. The total sample was collected from the students of tiniversiti Teknologi MARA and patients attending the dental clinic of Facult y of Dentistry Universiti Teknologi MARA who fulfilled the inclusion criteria. The study sample consists of 60 subjects from Malaysian Malay pure ethnic groups. The ages ranged between 20- 24 years old, equal from both genders (30 females and 30 males) selected under specific criteria.